Heirs' Responsibilities For Heirs' Debt From The Perspective Of Islamic Inheritance Law - Muhibbin, Moh.; Sunardi, Sunardi; Ansyah, Yudi (International Significance of Notary, 2024)
Abstract: Responsibility in the family context is very inherent and cannot be removed immediately. Like an heir, the heir is given responsibility when his parents during their lifetime carry out a legal act that causes a loss. The loss in question is an obstacle for other people who feel they have been harmed by an action carried out by the heir's parents during their lifetime. Losses give rise to a debt that must be paid off by anyone who owes it, but when someone is in debt he dies but cannot repay the debt, his heirs are obliged to pay off the debt made by his parents by reducing the assets left behind by his parents. In the context of Islamic inheritance law, debts must be paid even if the debtor has died and the person paying off the debt is the heir of the heir. However, what often comes to the fore in inheritance management is that one or more of the heirs do not agree with the other heirs. This disagreement will create and grow into an internal family conflict. There are two ways to resolve a problem if there is non-compliance between parties to carry out a fair distribution, namely by litigation and non-litigation. These two methods can be used in managing problems that occur, especially issues regarding inheritance.